ALKBH5 Inhibited Cell Proliferation and Sensitized Bladder Cancer Cells to Cisplatin by m6A-CK2α-Mediated Glycolysis - Hao Yu; Xiao Yang; Jinyuan Tang; Shuhui Si; Zijian Zhou; Jiancheng Lu; Jie Han; Baorui Yuan; Qikai Wu; Qiang Lu; Haiwei Yang (Elsevier, 2021)
N6-methyladenosine (m6A) is the most commonly occurring internal RNA modification to be found in eukaryotic mRNA and serves an important role in various physiological events. AlkB homolog 5 RNA demethylase (ALKBH5), an m6A demethylase, belongs to the AlkB family of dioxygenases and has been shown to specifically demethylate m6A in RNA, which is associated with a variety of tumors. However, its function in bladder cancer remains largely unclear. In the present study, we found that the expression of ALKBH5 was downregulated in bladder cancer tissues and cell lines. Low expression of ALKBH5 was correlated with the worse prognosis of bladder cancer patients. Furthermore, functional assays revealed that knockdown of ALKBH5 promoted bladder cancer cell proliferation, migration, invasion, and decreased cisplatin chemosensitivity in the 5637 and T24 bladder cancer cell lines in vivo and in vitro, whereas ALKBH5 overexpression led to the opposite results. Finally, ALKBH5 inhibited the progression and sensitized bladder cancer cells to cisplatin through a casein kinase 2 (CK2)α-mediated glycolysis pathway in an m6A-dependent manner. Taken together, these findings might provide fresh insights into bladder cancer therapy.